Developing an Integrated Project-Based Learning Application to Enhance Learning Practicals in Vocational Schools - Yulianus Zega; Dedy Irfan; M. Giatman; Ambiyar (Postgraduate, University of Mataram, 2025)
The implementation of a digital PjBL-based system significantly assists teachers in documenting practical learning and improving accountability for the learning process. The use of a digital PjBL management system not only increases student engagement but also significantly improves the quality of automotive engineering practice through progress tracking and real-time feedback.This study aims to design and develop a project-based learning (PjBL) management system suitable for automotive practice in vocational high schools and to assess its feasibility and effectiveness in enhancing student engagement and learning outcomes. The research employed a Research and Development (R&D) method adapted from the Borg & Gall and Sugiyono models. The developed web-based system features project management, evidence uploads, rubric-based assessments, discussion forums, and student progress monitoring. Validation was conducted by media experts and vocational practitioners, while limited trials involved 30 students from Grade XI of the Light Vehicle Engineering program. Results showed the system was highly feasible with an average score of 85.5%. The system improved student engagement scores from 3.04 to 4.3 and learning outcomes from 72.3 to 85.1. These findings confirm that a digital PjBL system effectively enhances practical learning in vocational education.